DEVELOPMENT OF TEACHING AND LEARNING MANAGEMENT MODEL USING THE DISTANCE LEARNING TELEVISION FOR BAN THUNG MAI SCHOOL UNDER THE SATUN PRIMARY EDUCATIONAL SERVICE AREA OFFICE - Yaba, Abdulaziz (Journal of Buddhist Anthropology, 2022)
The objectives of this research article were to 1) study current conditions and the need for teaching and learning management model using the distance learning television (DLTV), 2) develop teaching and learning management model using the DLTV, 3) try out teaching and learning management model using the DLTV, 4) evaluate the effective use of teaching and learning management model using the DLTV. This research was mixed methods approach: qualitative and quantitative research. The population included 33 students in grade 1, grade 3 and grade 6 and 3 teachers from Ban Thung Mai School in academic year 2019. Instruments used were a form of behavioral assessment, interview and group discussion. Percentage, mean ( ), standard deviation (SD), and content analysis were used for data analysis. The results showed that 1) the present condition, problems and demands of teaching and learning management model using the DLTV, participants with distinct positions expressed opinions toward problems concerning DLTV differently, and as perceived by participants were at a high level ( = 4.43), 2) the experts agree with the appropriateness and possibility of the model using the DLTV being usable at 100 percent, which means that this model can be used, 3) after using the teaching and learning management model using the DLTV, three teachers in the experimental group had higher skills than before the teaching and learning management using the DLTV were used, and also the students had higher learning achievement than before the teaching and learning management using the DLTV were used, 4) the evaluation of teaching skills and learning achievement after using the teaching and learning management model by the DLTV, teachers had higher skills and the students had higher learning achievement than before using the DLTV. All with a statistically significant difference at the 0.01 level.